2008
DOI: 10.1016/j.febslet.2008.02.044
|View full text |Cite
|
Sign up to set email alerts
|

Co‐activation of GABA receptors inhibits the JNK3 apoptotic pathway via the disassembly of the GluR6‐PSD95‐MLK3 signaling module in cerebral ischemic‐reperfusion

Abstract: In this study, we investigated whether the increase of inhibitory c-amino butyric acid (GABA) signal suppresses the excitatory glutamate signal induced by cerebral ischemia and the underlying mechanisms. In global cerebral ischemia, focal cerebral ischemia and oxygen-glucose deprivation, application of muscimol and baclofen, agonists of GABA(A) receptor and GABA(B) receptor, exerted neuroprotection. The agonists inhibited the increased assembly of the GluR6-PSD-95-MLK3 module induced by cerebral ischemia and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 30 publications
4
13
0
Order By: Relevance
“…Further validation of this difference was acquired from GABA B1 -nitrotyrosine double staining, which revealed the mutually exclusive expression of GABA B1 and nitrotyrosine. Our work confirms those previous studies [10,33,35,36] and further elucidates that the effect of FA against p38 MAP kinase-mediated apoptosis in the S-FA and R-FA groups is due to the enhancement of GABA B1 receptor expression at 24 h following reperfusion.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Further validation of this difference was acquired from GABA B1 -nitrotyrosine double staining, which revealed the mutually exclusive expression of GABA B1 and nitrotyrosine. Our work confirms those previous studies [10,33,35,36] and further elucidates that the effect of FA against p38 MAP kinase-mediated apoptosis in the S-FA and R-FA groups is due to the enhancement of GABA B1 receptor expression at 24 h following reperfusion.…”
Section: Discussionsupporting
confidence: 80%
“…Thus, GABA B receptors play a pivotal role in protecting against glutamate-induced apoptosis in a rat model of transient focal cerebral ischemia [34] . A number of studies have demonstrated a decrease in GABA B receptor expression 24 h after cerebral ischemia and that GABA B agonists could exert neuroprotection against glutamate-induced excitotoxicity via enhancing GABA B receptors [10,33,35,36] . In the present study, we found that FA firstly increased the expression of GABA B1 receptors in the www.nature.com/aps Cheng CY et al Acta Pharmacologica Sinica npg S-FA and R-FA groups at 3 h of reperfusion in spite of reduced nNOS and iNOS expression in the ischemic cortex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro, constituents of Valeriana officinalis mediate the release of c-aminobutyric acid and bind the same receptors as benzodiazepines, but with less affinity and milder clinical effects [38]. Recently, Dong-Han et al [39] has suggested that stimulation of the inhibitory GABA receptors can attenuate the excitatory JNK3 apoptotic signaling pathway via inhibiting the increased assembly of the GluR6-PSD-95-MLK3 signaling module in cerebral ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…92,93 Of the three isoforms of JNK (JNK1, 2 and 3), JNK3 was a good candidate to be a key molecule in the PrP C -dependent transmission of the excitotoxicity provoked by glutamate: (1) JNK3 is predominantly expressed in the CNS; 94 (2) Jnk3 knockout provides neuroprotection against various injuries, 95,96 and most interestingly, resistance to epileptic seizures and hippocampal cell death; 92 and (3) the JNK3 apoptotic signaling pathway is reported to be induced by KA and ischemia. 92,97 With these results in mind, we recently generated a double knockout mutant Prnp/Jnk3, which was insensitive to seizure and hippocampal cell death in response to KA injections. 44 This observation was corroborated in organotypic slices using pharmacological JNK inhibitors.…”
Section: Prpmentioning
confidence: 99%